Rat Bite Fever in an Elderly Patient With Dementia - Nakamoto, Yohei; Aita, Tetsuro; Imaoka, Koichi; Hamaguchi, Sugihiro (Annals of Internal Medicine: Clinical Cases, 2023)
Rat bite fever (RBF) is a zoonotic infection with nonspecific symptoms such as fever, myalgia, and arthralgia that mimic other systemic infections or noninfectious rheumatologic disorders. Obtaining a history of rat exposure is the key to diagnosis. Since a diagnosis may not be possible without some degree of suspicion, routine exposure history-taking is useful. We present the case of a woman with dementia and RBF whose history of a rat bite was obtained incidentally during routine history-taking from her spouse. Routine history about exposures should be taken for the diagnosis of RBF in patients with communication difficulties such as dementia.